Withanolides from three species of the genus Deprea (Solanaceae). Chemotaxonomical considerations - Casero, Carina Noelia (2015)
Nine withanolides were isolated from the aerial parts of Deprea bitteriana, Deprea cuyacensis, and Deprea zamorae. D. bitteriana yielded two withaphysalins, D. cuyacensis gave two 13,14-seco withaphysalins, while D. zamorae yielded five physangulidines. The compounds were fully characterized by a combination of spectroscopic methods (1D and 2D NMR and MS). All compounds isolated from D. bitteriana and D. cuyacensis were obtained as epimeric mixtures at C-18. The structure of physangulidine D was confirmed by X-ray diffraction analysis. The skeletons found in this research support the chemotaxonomical position of the genus Deprea in the tribe Physalideae.